A BRIEF REVIEW OF NUCLEAR-FACTOR-KAPPA-B IN SILICO STUDIES: Received: 10th May 2024, Revised: 12th June 2024, 5th July 2024, Accepted: 17th July 2024, Date of Publication: 14th November 2024 - Dayang-Sharyati D.A. Salam; Hwang Siaw San; Xavier Chee Wezen (LIFE: International Journal of Health and Life-Sciences, 2024)
This mini-review briefly summarises the use of computer-aided tools and research developments in nuclear-factor-kappa-b (NF-kB) within the last ten years. Computer-aided or in silico studies on the NF-kB complex give hope for developing potential therapeutic targets for various diseases involving the NF-KB protein. In silico investigations, as opposed to in vivo and in vitro research, have the advantages of being more exact and time-efficient and eliminating the utilisation of humans and animals. It provides a framework for evaluating the activity of prospective therapies against molecular targets, predicting their activity based on a compound’s structure even before it has been synthesised for additional in vitro and in vivo research. Targeting NF-kB protein is crucial as it can implicate many diseases, such as immune and inflammatory responses, involved in stress response, cellular growth, and apoptosis. These findings are critical for directing future research into the NF-kB protein, its function in human disorders, and prospective therapeutic targets.